2021
DOI: 10.1111/jfd.13368
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting Edwardsiella ictaluri‐induced mortality of riverine ayu, Plecoglossus altivelis (Temminck & Schlegel)

Abstract: We analysed the predisposing factors for Edwardsiella ictaluri infection in the riverine ayu Plecoglossus altivelis on the basis of environmental and epidemiological data obtained in a tributary to and the lower reaches of the Tama River, Japan, in July and August 2011–2015. Mortality of ayu due to E. ictaluri infection was observed only in the tributary in August 2012 and 2013; both periods were unusually hot. During these mortality events, daily average water temperatures rose approximately 3–4°C over 4–8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The survey revealed that E. ictaluri-related mortalities in ayu are exacerbated by adverse environmental conditions that include an increase in diurnal water temperature range (DWTR), high water temperatures, higher than normal air temperatures and lower levels of streamflows. 41 Naturally, E. ictaluri is mainly transmitted horizontally from dead infected catfish to naïve population due to infected fish cannibalization or E. ictaluri being shed from dead fish 39,42 whereas vertical transmission has not been reported yet 43 although the presence of the bacteria in gonads may imply possible vertical transmission. 44,45 A high bacterial count was also found in the vicinity of the dying fish which decreased with the removal of the dead fish whilst survivors of an epizootic become carriers and pathogen reservoirs.…”
Section: Pathog En D Iscovery Suscep Tib Le Hos Ts G Eog R Aphi C Al...mentioning
confidence: 99%
See 1 more Smart Citation
“…The survey revealed that E. ictaluri-related mortalities in ayu are exacerbated by adverse environmental conditions that include an increase in diurnal water temperature range (DWTR), high water temperatures, higher than normal air temperatures and lower levels of streamflows. 41 Naturally, E. ictaluri is mainly transmitted horizontally from dead infected catfish to naïve population due to infected fish cannibalization or E. ictaluri being shed from dead fish 39,42 whereas vertical transmission has not been reported yet 43 although the presence of the bacteria in gonads may imply possible vertical transmission. 44,45 A high bacterial count was also found in the vicinity of the dying fish which decreased with the removal of the dead fish whilst survivors of an epizootic become carriers and pathogen reservoirs.…”
Section: Pathog En D Iscovery Suscep Tib Le Hos Ts G Eog R Aphi C Al...mentioning
confidence: 99%
“…A recent epidemiological survey on environmental factors that influence E. ictaluri infection in riverine ayu was conducted in Japan over a 5‐year period. The survey revealed that E. ictaluri ‐related mortalities in ayu are exacerbated by adverse environmental conditions that include an increase in diurnal water temperature range (DWTR), high water temperatures, higher than normal air temperatures and lower levels of streamflows 41 …”
Section: Pathogen Discovery Susceptible Hosts Geographical Distributi...mentioning
confidence: 99%